Principles and Learning Models of Islamic Religious Education in Elementary Schools - Kosasih, Fitriyani; Saripudin, Saripudin; Saepulloh, Asep (Edumaspul: Jurnal Pendidikan, 2023)
Learning principles can be used to reveal the limits of possibilities in learning, so that teachers can take appropriate actions This study aims to discuss the principles and models of PAI learning in elementary schools, with the hope that understanding the principles and learning models that are appropriate for PAI makes it possible in the future to be able to reformulate Islamic education learning systems to make them more functional. The main problem discussed in this paper is how the principles and learning models of Islamic Religious Education are. The results of this study indicate that in Islamic education learning activities in elementary schools, a teacher must use certain learning theories and principles in order to guide the teacher’s activities in planning and implementing learning activities. Learning principles can be used to reveal the limits of possibilities in learning, so that teachers can take appropriate actions. Apart from that, with the theory and principles of learning, teachers can also have and develop the attitudes needed to support the improvement of student learning. PAI teachers can innovate to create their own learning model to be used. This is because the teacher is the person who best understands the characteristics and needs of their students